Does uptake of specialty care affect HRQoL development in COPD patients beneficially? A difference-in-difference analysis linking claims and survey data - Alisa Stöber; Pavo Marijic; Christoph Kurz; Larissa Schwarzkopf; Florian Kirsch; Anja Schramm; Reiner Leidl (The European Journal of Health Economics, 2023)
Background: There is an evidence gap on whether the choice of specialty care beneficially affects health-related quality of life (HRQoL) in patients with chronic obstructive pulmonary disease (COPD). This study analyzes how newly initiated pulmonologist care affects the generic and disease-specific HRQoL in COPD patients over a period of 1~year. Methods We linked claims data with data from two survey waves to investigate the longitudinal effect of specialty care on HRQoL using linear Difference-in-Difference models based on 1:3 propensity score matched data. Generic HRQoL was operationalized by EQ-5D-5L visual analog scale (VAS), and disease-specific HRQoL by COPD assessment test (CAT). Subgroup analyses examined COPD patients with low (GOLD AB) and high (GOLD CD) exacerbation risk. Results In contrast to routine care patients, pulmonologists' patients ( n 0.167em=0.167em442) experienced no significant deterioration in HRQoL (VAS -~0.0, p 0.167em=0.167em0.9870; CAT0.167em+0.167em0.5, p 0.167em=0.167em0.0804). Models unveiled a small comparative advantage of specialty care on HRQoL (mean change: CAT -~0.8, VAS0.167em+0.167em2.9), which was especially pronounced for GOLD AB (CAT -~0.7; VAS0.167em+0.167em3.1). Conclusion The uptake of pulmonologist care had a statistically significant, but not clinically relevant, beneficial impact on the development of HRQoL by slowing down overall HRQoL deterioration within 1~year. Including specialty care more appropriately in COPD management, especially at lower disease stages (GOLD AB), could thus improve patients' health outcome.
Keywords: I11; H43; 610; EQ-5D-5L; COPD assessment test; Longitudinal study; Real-world evidence; Specialty care; Pulmonologist